2021
DOI: 10.3390/insects13010008
|View full text |Cite
|
Sign up to set email alerts
|

Lobesia botrana: A Biological Control Approach with a Biopesticide Based on Entomopathogenic Fungi in the Winter Season in Chile

Abstract: Lobesia botrana (Denis and Shiffermüller) (Lepidoptera: Tortricidae) is one of the main pests that affect the production and export of table grapes in Chile. Because this pest has quarantine status, the fruit must be fumigated with methyl bromide, which reduces the fruit’s export competitiveness in the destination market. In the present study, to help resolve this issue, six native entomopathogenic fungi were identified through multilocus analysis, including three Beauveria pseudobassiana and three Metarhizium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The identification of B. peudobassiana RGM 2184 was previously performed by Altimira et al (2022) [ 3 ] using multilocus analysis of only four molecular markers (bloc, tef, rpb1, and rpb2). In this study, taxonomic identification of this strains was confirmed using a phylogenetic analysis of 25 universal ribosomal proteins ( Figure 1 ), together with nucleotide similarity parameters such as ANI and dDDH ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of B. peudobassiana RGM 2184 was previously performed by Altimira et al (2022) [ 3 ] using multilocus analysis of only four molecular markers (bloc, tef, rpb1, and rpb2). In this study, taxonomic identification of this strains was confirmed using a phylogenetic analysis of 25 universal ribosomal proteins ( Figure 1 ), together with nucleotide similarity parameters such as ANI and dDDH ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…This capability allows their use as an alternative to chemical insecticides for pest control [ 2 ]. The genera Metarhizium , Beauveria , Cordyceps , and Akanthomyces are the most used for pest control because they are relatively easy to grow en masse, have a wide range of hosts, and exhibit similar efficacy to commercial insecticides [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPF strain B. pseudobassiana RGM 2184 was obtained from the Chilean Culture Collection of Microbial Genetic Resources of the Agricultural Research Institute (Instituto de Investigaciones Agropecuarias, Santiago, Chile). Strain RGM 2184, isolated from southern Chile, is native to areas with low temperatures and high humidity [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…This tissue protects the pupae from low temperatures, water, predators, and even agrochemicals. Formulations using the entomopathogenic fungus Beauveria pseudobassiana S.A Rehner and Humber (Hypocreales: Cordycipitaceae) as the active ingredient have demonstrated the ability to control L. botrana in the diapause stage and to penetrate its cocoon’s silk ( Figure S1 ) [ 13 ]. A wettable powder formulation of the B. pseudobassiana RGM 2184 strain was shown to achieve a maximum efficacy level of 80% against pupae of L .…”
Section: Introductionmentioning
confidence: 99%